2020
DOI: 10.3390/dj8030073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tooth Factors and Procedural Errors on the Incidence and Severity of Post-Endodontic Pain: A Prospective Clinical Study

Abstract: The objective of this prospective study was to assess tooth-related factors that play a role in the incidence of postoperative pain (PP) and determining if procedural errors influence PP occurrence. A total of 442 patients referred for root canal treatment met the inclusion criteria and were included in this prospective study. The same protocol was used in all root canal treatments. Patient, tooth, treatment related factors and the occurrence of procedural errors were registered. Incidence and intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Arias et al 2013 ( 16) reported that spontaneously triggered post-operative pain was the most commonly reported type of discomfort, which is in agreement with the current results. Occlusal contact was not relieved in the present study inorder to stimulate the worst-case scenario for evaluating post-operative pain as the presence of occlusal contact has been associated with increased post-treatment discomfort (10, 16). Despite this, the post-operative pain occurrence was similar to other reports on pain following root canal treatment (16), thereby confirming the efficacy of laser application.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Arias et al 2013 ( 16) reported that spontaneously triggered post-operative pain was the most commonly reported type of discomfort, which is in agreement with the current results. Occlusal contact was not relieved in the present study inorder to stimulate the worst-case scenario for evaluating post-operative pain as the presence of occlusal contact has been associated with increased post-treatment discomfort (10, 16). Despite this, the post-operative pain occurrence was similar to other reports on pain following root canal treatment (16), thereby confirming the efficacy of laser application.…”
Section: Discussionmentioning
confidence: 88%
“…A 10-point VAS was employed as our previous studies with irreversible pulpitis (3, 5, 10, 11) followed this similar protocol, which allowed us to have standardised metrics for efficient patient communication. Additionally, most of the patients encountered in the authors’ department have limited education which would greatly impair their interpretation of a pain scale with more than 10-points.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gender there is no agreement in the literature about its role on postoperative pain incidence following endodontic treatment, with certain observations concluding that gender has no influence, the subjective component of the pain experience is probably the reason why gender varies among the different studies 26 . It is controversial between many studies that tested the influence of gender on postoperative pain as there were always variations some proved that males had significantly higher pain scores compared to females 24 , others referred to females having higher postoperative pain levels 27 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong correlation found between preoperative pain and the incidence of postoperative pain 27 , and the presence and severity of preoperative pain has a strong effect on the development of pain after endodontic intervention 6 . Patients with increased preoperative pain have a higher risk of experiencing postoperative pain 26 . The core endodontic literature agreed that endodontic treatment significantly reduces preoperative pain proving that the approach used is effective in treating pain 25 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the goals of endodontic treatment is to decrease the post endodontic pain as well as to preserve the compromised tooth structure to maintain function 1 . Post endodontic pain can be defined as the unpleasant sensation following root canal treatment that is reported in 3%-65% of the cases 2 .…”
Section: Introductionmentioning
confidence: 99%